2018
DOI: 10.31768/2312-8852.2018.40(3):218-222
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the Epithelial-Mesenchymal Transition in Cells of Endometrial Carcinoma

Abstract: Aim: To study the expression of adhesion markers (E-cadherin, β-catenin and vimentin) associated with epithelial-mesenchymal transition (EMT) and their role in progression of endometrial carcinoma (EC). Materials and Methods: Expression of E-cadherin, β-catenin and vimentin was studied immunohistochemically in the samples of surgical material of 55 EC patients stage I–III. The proliferation index was determined by flow cytometry. Results: In the group of vimentin-negative EC, tumors of low differentiation grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Overexpression of vimentin correlates significantly with poor prognosis in several cancers, such as gastric cancer and breast cancer [11,12]. Conversely, previous studies showed that vimentin immunoreactivity was common in normal proliferative endometrium, and its persistence in EC might indicate a less malignant phenotype [13][14][15]. For example, Papadopoulos et al [14] demonstrated that expression of vimentin decreased as a lesion progressed to malignancy, and a recent study by Nesina et al [15] also found that decreased expression of vimentin in EC correlated with the aggressiveness of tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of vimentin correlates significantly with poor prognosis in several cancers, such as gastric cancer and breast cancer [11,12]. Conversely, previous studies showed that vimentin immunoreactivity was common in normal proliferative endometrium, and its persistence in EC might indicate a less malignant phenotype [13][14][15]. For example, Papadopoulos et al [14] demonstrated that expression of vimentin decreased as a lesion progressed to malignancy, and a recent study by Nesina et al [15] also found that decreased expression of vimentin in EC correlated with the aggressiveness of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, previous studies showed that vimentin immunoreactivity was common in normal proliferative endometrium, and its persistence in EC might indicate a less malignant phenotype [13][14][15]. For example, Papadopoulos et al [14] demonstrated that expression of vimentin decreased as a lesion progressed to malignancy, and a recent study by Nesina et al [15] also found that decreased expression of vimentin in EC correlated with the aggressiveness of tumors. However, there are only a few studies thus far focusing on the relationship between vimentin expression and EC prognosis currently, and its underlying molecular mechanism in EC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The tumours of 69.5% of patients with stage I-II EC and 50.0% tumours of patients with stage III of tumour progression were positive in terms of the expression of this protein. It was determined that positive expression of Twist was associated with the decreased expression of E-cadherin and the increased expression of vimentin as compared with these indices for ECE with negative expression of Twist [16,18] (Tab. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained were compared with the results of the previous studies, in which the authors determined the expression of EMT markers in these very cases of ECE [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, vimentin expression, mesenchymal transcription factors, and cancer stem cell markers are increased. In endometrial carcinoma, EMT has been associated with all events of progression 119 . Cells emerging from EMT show expression of the CD133 marker and have the ability to self-renew, migrate, and increased drug resistance 120 .…”
Section: Box 2 Conserved Process In Epithelial Carcinogenesismentioning
confidence: 99%